Epidemiology, Prevention and Management of Hypertension in Young Athletes: A Narrative Review - Hejnosz, Aleksandra; Piątek, Maja; Jastrzębski, Michał; Szczerba, Mateusz; Knysak, Karol; Maj, Alicja; Wilkowska, Krystyna; Kaczorowski, Wojciech; Michałowski, Maciej; Sudomir, Maria (Quality in Sport, 2025)
Hypertension is one of the most prevalent global health challenges and increasingly affects children and adolescents. Despite well-established cardiovascular benefits of physical activity, recent evidence shows that young athletes are not uniformly protected from elevated blood pressure (BP). They may exhibit unique hemodynamic characteristics shaped by training load and sport-specific demands. This narrative review synthesizes original research published between 2015 and 2025 on the epidemiology, determinants, prevention strategies, and diagnostic considerations of hypertension in adolescent athletes. Eight studies identified through structured searches indicate that elevated BP is relatively common, with prevalence similar to that in the general adolescent population. Excess body weight, sport specialization, and fitness variability contribute substantially to BP elevation. Several studies link elevated BP with early cardiac remodeling, highlighting potential long-term implications even in highly trained youth. Lifestyle interventions, including moderate-to-vigorous activity, targeted conditioning, and improved fitness, support BP regulation. Fitness domains such as aerobic capacity, flexibility, and muscular power independently correlate with BP, emphasizing multifactorial prevention. Diagnostic evaluation requires consideration of athletic physiology. Standardized measurements, repeated assessments, exercise BP testing, and context-specific interpretation, particularly distinguishing physiological adaptations from early pathological changes, are essential for accurate diagnosis and safe sport participation. Overall, hypertension in young athletes remains underrecognized but clinically relevant. Early detection, fitness-oriented prevention, and tailored diagnostic approaches are key to safeguarding cardiovascular health and supporting athletic performance.